Evaluating Alternative Investment Options for Grinding Machines Using the Incremental Cost Method - Arifah, Fatayaturrokhma Ilmala; Chumaidiyah, Endang; Suryana, Nanang (JTI: Jurnal Teknik Industri, 2024)
production capacity constraints. A key issue is the limited capacity of the grinding machine, which frequently overheats, leading to production delays and exceeding standard working hours. To address this problem, an investment in an additional grinding machine is proposed. A feasibility study was conducted by analyzing market, technical, and financial aspects using Net Present Value (NPV), Internal Rate of Return (IRR), and Payback Period (PBP). The results showed an NPV of IDR 4,824,298,738, an IRR of 34.72%, and a PBP of 3.85 years, indicating the investment’s feasibility. Additionally, an incremental cost analysis was performed to compare the existing condition with the proposed alternative, yielding a ∆ROR of 98%, which exceeds the Minimum Attractive Rate of Return (MARR) of 11.01%. These findings confirm that adding a grinding machine is the most viable alternative to enhance production capacity, accommodate growing demand, and improve operational efficiency. By implementing this investment, the company can optimize its production process, reduce overtime costs, and ensure a stable supply to meet market needs. The feasibility study provides valuable insights for decision-making in similar industries facing production limitations due to equipment constraints.Keywords: Feasibility Analysis, Incremental Cost Analysis, NPV, IRR, PBP